Zagadnienie reintegracji terytorium państwa a prawo ludu do samostanowienia - Tyranowski, Jerzy (Wydział Prawa i Administracji UAM, 1988)
During a decolonization process there appeared a complicated problem of non-self-governing territories which earlier, i.e. in the period of their colonization, had been separated from states existing until today. Some of such states raise claims to restoration of integrity of the territory which was earlier subjected to colonial authority. Legal character of such claims was in particular acknowledged in the International Court of Justice advisory opinion on Western Sahara. Thus within the decolonization process — and only then — may territorial claims founded on historical titles be raised. A characteristic feature of such claims is that they are not directed against territorial integrity of any state: they concern colonial territories. Yet they may still collide with a right of a given colonial people to self-determination. Hence, what prevails in such a situation: a claim of a state to restoration of its territorial integrity or a right of a colonial people to self-determination? Having analysed the best known situations (Goa, gong-Kong, Makau, East Timor, Belize, The Falklands-Malwins, Gibraltar, Western Sahara) the author attempts to formulate several conclusions in that respect. The author is first of all of the opinion that in view of common recognition of a right of colonial peoples to independence a former title to sovereignity should in no circumstance precede over a right of those peoples to self-determination. If a given colonial territory existed for a long time under a recognized status of non-self-governing territory and now a people living on that territory expresses its will of retaining that separate status through forming its own state, then such a situation may resemble an act of a successful secession: a claim to restoration of territorial integrity is no longer allowed. The above conclusion is all the more justified in cases of former colonial territories where newly independent states have already been established. A different situation arises with respect to colonial territories with population not constituting a people in the sense of a right to self-determination. Here, in the absence of other criteria distinguishing a people as a bearer of a right to self-determination, the basis for a solution may be only the principle of effectiveness. Only on the strength of criteria resulting from the said principle may a refusal to recognize a right to sovereignity of inhabitants of a colonial territory (i.e. a refusal to recognize them as „a people") be justified. In such cases claims to restoration of territorial integrity are allowed. Moreover, in view of the requirement of a complete abolishment of colonialism, such restoration of integrity seems to be the only possible solution.
The problems of restoration of territorial integrity of a state and a right of a people to seld-determination